Prospective territoriale en terre de développement durable : une application à la région Guadeloupe - Yvette Lazzeri; El Mouhoub Mouhoud (Études Caribéennes)
Sustainable Region should position itself in a context of openness and territorial competition. Without the ability to significantly influence the parameters of global change, the actors are called upon to anticipate and take them into account in their strategies. They are encouraged to develop a future vision that renews their relationship to the territory in the context of sustainable development. It is in this spirit that Territorial Prospective exercise was developed. The method presented here for the Guadeloupe region, integrates both trends related to the contextual environment and trends specific to the territory. Beyond a scenario over water which can lead to a marginalization of the region, two visions of the future are analyzed Guadeloupe ... towards one unacceptable and one desirable.